The costs of recruiting apprentices : evidence from German firm-level data - Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Wenzelmann, Felix [Verfasser] (My University, 2015)
"In this paper, we use firm-level data to analyse a firm's costs of recruiting apprentices in Germany. We find that recruitment costs amount on average to 600 Euros per hire (approximately one month of apprentice pay or 1-2 per cent of a firm's training expenditures), but costs are heterogenous across firms and vary strongly with the training occupation. Our results suggest that shortages in the local supply of apprentices and a high degree of competition among training firms in the region increase recruitment costs. Furthermore, we find that firms with a works council or an investment-oriented training strategy incur higher recruitment costs. Finally, marginal recruitment costs first increase but eventually decrease for firms hiring a large number of apprentices. Our results are important in light of the increasing firm competition for talented school leavers induced by demographic change." (Authors' abstract, BIBB-Doku)
Aktualisierte Fassung der ersten Version von Dezember 2013. Diese erste Version wurde in der BIBB-Jahresbibliografie 2013 berücksichtigt.
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 5.3 Personalentwicklung; S 4 Kosten & Finanzierung; Betriebliche Berufsausbildung; Ausbildungsverhalten; Personalgewinnung; Kosten; Ausbildungsinvestition; Einflussfaktor